Sequencing of Proteus Toxic Agglutinin (Pta) Gene in Proteus Mirablis and Cytotoxic Effect of Pta on Human Colon Cancer Cell and Human Kidney Cell - Lamees A. Abdul-Lateef (Journal of Global Pharma Technology, 2017)
Objective study the sequencing of Pta gene and the cytotoxic effect of pta gene on SW480 and ACHN cell line Material and method detection of pta gene by using PCR technique, detection of mutation in the Pta gene by used automated sequencing. Also the cytotoxic effect of Pta toxin on cell lines of SW480 and ACHN cell were used in vitro. Results the result was revealed that the Pta gene is present in 17 isolates (15 isolated from urine and 2 isolates from stool). Sequencing of Pta gene from isolates of Proteus mirablis reveals of 43 mutations in five isolates and gives identity in percentage (92-95%) with standard strand in NCBI web site. However, the cytotoxic effect of Pta on cells line of SW480 and ACHN were used in vitro was also investigated. The result was shown that the effect of Pta toxin on SW480 lead to the proliferation of cell was significantly elevated when Pta toxin at 12.5%, 25%, and 50% concentrations. The concentration 50% of Pta toxin a significantly better effect on cell growth On the other hand, ACHN cell was gradually increase in growth at concentrations (6.25%, 12.5%%, 25%, and 50%)Keywords: Proteus toxic agglutinin gene, Sequencing, Human colon cancer cell line, Human kidney cell line.